Enzymatic activity of Beauveria bassiana and Metarhizium anisopliae lipases and proteases and their relationship with pathogenicity to the coffee berry borer Hypothenemus hempei (Coleoptera: Scolytidae) - GIRALDO-CARDOZO, ELSA MARÍA; LÓPEZ-F., YAMEL; DELGADO-B., FERNANDO; VÉLEZ-A., PATRICIA E. (Revista Colombiana de Entomología, 2001)
The use of entomopathogenic fungí like Beauveria bassiana and Metarhizium anisopliae have shown great potential as a control method of several insects like the coffee berry borer (Hypothenemus hampei). A close relationship between the activity of some enzymes that attack the cuticle structural components and the infection process of the fungí over the insect has been found. At first stage, the growing rate. culture medium pH changes, pathogenicity, and enzymatic activity (total proteases and lipases) in Bb 9620 (monosporic) and Bb 9205 (multisport) of B. bassiana isolations and Ma 9303 (monosporic) and Ma 9236 (multisporic) of M. anisopliae isolations were quantified. At the second stage, nine isolations of B. bassiana and five of M. anisopliae with different pathogenicity levels over H. hampei were studied. The enzymatic activity was measured by spectrophotometry using extinction coefficients of e340=98 M-1cm-1 for the azo group released by the proteases and e400 = 18. 77M-1cm-1 for the p-nitrophenol released by lipases. The total proteases show maximum activity peaks between the fifth and seventh days of incubation. The M. anisopliae proteolytic activity is significative higher (p<0.05) than B. bassiana activity. The total lipases showed maximum activity between the third and fifth days of incubation, but there is no significant difference among isolates. The results point out that both lipases and proteases play an important role at the initial infection mechanism of fungí over the H. hampei cuticle.